Nanopore size growth and ultrafiltration performance of SnO2 ceramic membranes prepared by sol-gel route - Santos, LRB; Santilli, Celso Valentim [UNESP]; Larbot, A.; Persin, M.; Pulcinelli, Sandra Helena [UNESP] (Kluwer Academic Publ, 2000)
Supported ceramic membranes have been produced by the sol-casting procedure from aqueous colloidal suspensions prepared by the sol-gel route. Coatings on a tubular alumina support have been successfully performed leading to crack free layers. Samples have been sintered at 400, 500 and 600 degreesC, and the effect of heating treatment on the nanostructure and on the ultrafiltration properties are analyzed. The characterization has been done by high resolution scanning electron microscopy, nitrogen adsorption-desorption isotherms, water permeation and cut-off determination using polyethylene glycol standard solutions. The micrographs have revealed that grains and pore size increase with the temperature, whereas their shape remains invariant. This results is in agreements with N-2 adsorption-desorption analyses, which have revealed that the mean pore size diameter increases from 4 to 10 nm as the sintering temperature increases from 400 to 600 degreesC, while the total porosity remains constant. Furthermore, the tortuosity, calculated from water permeability, is essentially invariant with the sintering temperatures. The membranes cut-off, determined with a retention rate equal to 95%, are 3500, 6500 and 9000 g . mol(-1) for 400, 500 and 600 degreesC, respectively, showing that the permeation properties of SnO2 ultrafiltration membranes can easily be controlled by sintering condition.
Keywords: SnO2 membrane; nanopores growth; water permeation; nanofiltration cut-off